Scalable Network Monitoring in High Speed Networks - Choi, Baek-Young; Zhang, Zhi-Li; Du, David Hung-Chang (Springer eBooks., 2011)
Network monitoring serves as the basis for a wide scope of network, engineering and management operations. Precise network monitoring involves inspecting every packet traversing in a network. However, this is not feasible with future high-speed networks, due to significant overheads of processing, storing, and transferring measured data. Network Monitoring in High Speed Networks presents accurate measurement schemes from both traffic and performance perspectives, and introduces adaptive sampling techniques for various granularities of traffic measurement. The techniques allow monitoring systems to control the accuracy of estimations, and adapt sampling probability dynamically according to traffic conditions. The issues surrounding network delays for practical performance monitoring are discussed in the second part of this book. Case studies based on real operational network traces are provided throughout this book. Network Monitoring in High Speed Networks is designed as a secondary text or reference book for advanced-level students and researchers concentrating on computer science and electrical engineering. Professionals working within the networking industry will also find this book useful.